Pyroptosis mediates osteoporosis via the inflammation immune microenvironment - Chen, Te; Jin, Linyu; Li, Jingyi; Liu, Yikai (Frontiers in Immunology, 2024)
Osteoporosis represents a systemic imbalance in bone metabolism, augmenting the susceptibility to fractures among patients and emerging as a notable mortality determinant in the elderly population. It has evolved into a worldwide concern impacting the physical well-being of the elderly, imposing a substantial burden on both human society and the economy. Presently, the precise pathogenesis of osteoporosis remains inadequately characterized and necessitates further exploration. The advancement of osteoporosis is typically linked to the initiation of an inflammatory response. Cells in an inflammatory environment can cause inflammatory death including pyroptosis. Pyroptosis is a recently identified form of programmed cell death with inflammatory properties, mediated by the caspase and gasdermin families. It is regarded as the most inflammatory form of cell death in contemporary medical research. Under the influence of diverse cytokines, macrophages, and other immune cells may undergo pyroptosis, releasing inflammatory factors, such as IL-1β and IL-18. Numerous lines of evidence highlight the pivotal role of pyroptosis in the pathogenesis of inflammatory diseases, including cancer, intestinal disorders, hepatic conditions, and cutaneous ailments. Osteoporosis progression is frequently associated with inflammation; hence, pyroptosis may also play a role in the pathogenesis of osteoporosis to a certain extent, making it a potential target for treatment. This paper has provided a comprehensive summary of pertinent research concerning pyroptosis and its impact on osteoporosis. The notion proposing that pyroptosis mediates osteoporosis via the inflammatory immune microenvironment is advanced, and we subsequently investigate potential targets for treating osteoporosis through the modulation of pyroptosis.